CYBERSLACKING : A LITERATURE REVIEW OF NON-ACADEMIC MEDIA MULTITASKING OF UNIVERSITY STUDENTS - Simanjuntak, Ermida; Nawangsari, Nur Ainy Fardana; Ardi, Rahkman (Journal of Educational, Health and Community Psychology, 2018)
AbstractUniversity students use internet in daily life ranging from learning, socializing and recreation purposes. Cyberslacking in the campus relates to the topic of non-academic media multitasking among university students. Media multitasking defines as connecting to more than one media simultaneously and cyberslacking is activities with media multitasking in the context of non-academic internet access during lectures. This present study will review some researches on cyberslacking and non-academic media multitasking in the context of university students. The review findings conclude that cyberslacking is also media multitasking in the context of non-academic internet access during lectures. Media multitasking could be distinguished between learning related activities and unlearning related activities and cyberslacking is regarded as unlearning related activities. Students who do cyberslacking mostly engage in social networking sites during media multitasking behaviors. Some studies discuss the impact of cyberslacking and non-media multitasking to academic performance. Other studies also mentioned about self regulation and self efficacy as important variables that relate to cyberslacking and non-academic media multitasking. Further researches on cyberslacking should be considered building theoretical model of cyberslacking in the educational setting as well as the development of measurement tools for academic cyberslacking behaviors. Keywords : cyberslacking, non-academic media multitasking, university students